Legal Protection for Consumers for Excessive Claims in Skincare Product Contents - Putri Melani Tampubolon; July Esther; Ria Juliana Siregar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines legal protection for consumers against overclaim practices in skincare product ingredients. This phenomenon is widespread in e-commerce, where consumers are often influenced by trends and fail to thoroughly examine product quality. Overclaim practices, such as listing an active ingredient percentage that does not match the actual content, have harmed consumers both financially and health-wise. This research employs a normative method with a legislative and conceptual approach, referring to Law Number 8 of 1999 on Consumer Protection and relevant BPOM (Indonesian Food and Drug Authority) regulations. The findings indicate that consumer protection encompasses fundamental rights, including accurate information and compensation for damages. Preventive measures include regulations, BPOM supervision, consumer education, and the role of institutions such as BPSK (Consumer Dispute Resolution Agency) and BPKN (National Consumer Protection Agency). Meanwhile, repressive efforts involve dispute resolution through litigation and non-litigation channels. This study highlights gaps in the effectiveness of regulations and oversight of overclaims, as well as the need for practical solutions, including more extensive consumer education.